Effects of Connection Stiffness and Plasticity on the Service Load Behavior of Unbraced Steel Frames - Bhatti, M. Asghar; Hingtgen, James E. (Engineering Journal, 1995)
Accurate determination of the relative restraint of beam-to-column connections is important for both the strength and serviceability of structural frames. Overestimating the connection restraint can result in underestimating lateral sway and underestimating the connection restraint can lead to underestimating forces developed in the beams and columns. Both conditions can influence structural instability. This paper examines the effects that certain connection parameters have on the serviceability limit state of unbraced steel frames. The connections are modeled as elastic-perfectly plastic and are described by their elastic stiffness and the ultimate moment capacity. The second order P-delta effects are included. The effect of connection geometry on lateral sway for an unbraced, 3-bay and 5-story office building is studied. Three types of bolted connections: single and double web-angle, top- and seat-angle, and top- and seat-angle with double web-angles are examined and their effect on lateral sway is compared with and without second order P-delta effects.